Influence of Deformation and Instability of Borehole on Gas Extraction in Deep Mining Soft Coal Seam - Xue-Bo Zhang; Shuai-Shuai Shen; Xiao-Jun Feng; Yang Ming; Jia-jia Liu (Advances in Civil Engineering)
To study the effects of the three deformation instability modes of gas drainage borehole on gas drainage, the deformation instability mechanism of soft coal seams is analyzed, three deformation instability modes are proposed for soft coal seams, namely, complete holes, collapse holes, and plug holes, and a solid-fluid coupling model incorporating dynamic change of borehole suction pressure is established. The results of the study show the following. (1) When there is no borehole deformation (i.e., complete borehole), the suction pressure loss of drainage system in the borehole is very small, whose effect on gas drainage can be neglected. (2) In case of borehole collapse, the suction pressure loss is big at the collapse segment, and the total suction pressure loss of the drainage system in the borehole is bigger than that in the complete hole. However, it is smaller than the suction pressure of the drainage system and exerts limited effect on gas drainage. As the borehole collapse deteriorates, the effective drainage section of the borehole becomes smaller, while the suction pressure loss in the borehole increases continuously; thus, the gas drainage effect continuously worsens. (3) In case of plug hole, a continuous medium forms between the plug segment coal body and the surrounding coal seam, the plug segment drainage pressure turns into coal-bed gas pressure, and effective drainage length of the borehole shortens, seriously affecting the gas drainage effect. The study carries important theoretical guiding significance for improving gas drainage effect and effectively preventing gas disasters.